Pengembangan Aplikasi Pembukuan Pada UMKM MN Djamboe Berbasis Bootstrap Dengan Metode Waterfall - Gufron, Gufron (Jurnal Media Informatika, 2024)
Micro, small and medium enterprises have a very important role in the economy in Indonesia, because they make a major contribution to creating jobs and increasing people's income. However, MSMEs often face various obstacles in terms of bookkeeping and developing businesses into more professional creative industries. One of the causes is limited knowledge and skills in financial management. So that the financial reports produced do not reflect the actual business conditions, which can hinder the right business decision-making. In addition, business actors consider focusing on their business activities more important than learning or making financial books. The inability to see a clear financial picture can make MSMEs vulnerable to mismanagement of funds, which can lead to serious financial problems. To overcome these obstacles, one solution that can be done is to develop an application that can help MSMEs in making financial books easily. In collecting data, observation, interview and literature study methods are used, while the waterfall method is used to develop the application. The application is made using the PHP programming language with the MariaDB database and bootstrap is used so that the application built is interactive and comfortable to access from various types of devices. Application testing using the blackbox method shows that all user needs can be met properly. This research proves that information technology-based applications are easy for business actors to use in making financial bookkeeping.